The Contourlet-based structural similarity for image quality evaluation - Yan, Zhidan; Li, Junxiang; Yang, Chunmei (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Taking into account the fact that the judgment on image quality by human eyes is more dependent on the main contours of an image, the Contourlet-based structural similarity method (CSSIM) is introduced and analyzed in the paper. The outline information of an image can be extracted through multi-scale decomposition process. The simulated experiments show that CSSIM is more consistent with visual characteristics of human eyes and better than the common quality evaluation method of structural similarity (SSIM) to judge the image quality.